Study on teratogenic effects of methotrexate; Alteration of gene expression pattern in human placenta choriocarcinoma (JEG-3) cells - Lee, Jina; Kim, Youn-Jung; Ryu, Jae-Chun (KOREAN BIOCHIP SOCIETY-KBCS, 2010)
Methotrexate is a well known chemotherapeutic agent, extensively used for leukemia and other cancers. Although its efficacy is wide, methotrexate can cause serious or life-threatening toxicities on liver, lungs, kidney, and immune system. Teratogenicity is one of the methotrexate-induced side effects. So, we performed with JEG-3, human placenta choriocarcinoma cell line, to identify the differentially expressed genes (DEGs) related to teratogenicity of methotrexate using an Agilent 44-K whole human genome chip. Through the analysis of gene expression profiles, we identified 887 up-regulated genes and 828 down-regulated genes above 1.5-fold by methotrexate. At IC30 doses recognized genes were functionally categorized as being involved in purine and pyrimidine biosynthetic process, cell cycle arrest, and apoptosis. Functionally important purine and pyrimidine biosynthesis-related genes were further validated by real-time RT-PCR. The results showed that GART, HPRT1, TYMS, and CTPS genes altered their expression levels by methotrexate. Alteration of these genes may lead to methotrexate-induced teratogenicity, which caused by imbalance of nucleotide biosynthesis. In conclusion, both gene expression profiles and functional analysis have identified potential gene-based biomarkers and provided insights into the mechanism underlying the response of human placenta cell line to methotrexate exposure.
Keywords: HIGH-DOSE METHOTREXATE; RHEUMATOID-ARTHRITIS; RATIONALE; PREGNANCY; RESCUE